Prospective evaluation of facial and masticatory muscles activity in different malocclusion patients : an electromyography study - Nishi, Shamima Easmin (2020)
Mastication procedure involves muscular activity by chewing, swallowing and digestion of food where the occlusal surfaces of the teeth are involved for crushing and grinding of solid foods. It is well established that malocclusion patient exhibits a decrease in masticatory performance when compared with normal occlusion. This study aimed to investigate and compare the effect of the facial (buccinator and orbicularis oris) and masticatory (masseter and temporalis) muscle activity via surface electromyography (sEMG) in orthodontic patients pre and at 6 months of the orthodontic treatment. Malay patients with different types of malocclusion (Class I, II div 1, II div 2 and III) were selected through screening from the Specialist Orthodontic Clinic, Hospital Universiti Sains Malaysia. After taking the informed consent, patients were randomized, and the treatment plan was done with the final diagnosis. According to the objectives and sample size, patients were subdivided into different groups such as laser and non-laser groups; extraction and non-extraction groups and three different brackets groups (conventional, self-ligating and ceramic brackets). sEMG of muscles were done by using a two-channel electromyography device, where pre-gelled and self-adhesive electrodes (bilateral) were used. sEMG activity of masseter, temporalis, buccinator and orbicularis oris muscle were recorded during different action (chewing, clenching, blowing and smiling) before and at six months of fixed orthodontic treatment. In the statistical analysis, Class II div 1 malocclusion presented with higher muscle activity in comparison to Class I, Class II div 2 and Class III malocclusion. There was a significant difference found in the chewing activity of the right masseter muscle (P= 0.025) with different overjet. Furthermore, malocclusion patients with different overbite showed a significant difference in blowing activity of lower orbicularis oris during 1st blow (P=0.007), 2nd blow (P=0.005), the high peak of 1st blow (P=0.014) and the high peak of 2nd blow (P=0.011). The present study showed a significant difference in right buccinator muscle activity during 1st smile (P= 0.040) with different face profile. However, the smiling activity of upper orbicularis oris showed significant differences during rest (P= 0.048), 2nd smile (P= 0.038), the high peak of 1st smile (P= 0.041) and the high peak of 2nd smile (P= 0.032) with different lip competency. Analysis of repeated measured ANOVA showed a significant difference in muscle activity between extraction and non-extraction treatment procedure. The patient who received conventional bracket for orthodontic treatment showed higher EMG activity in compare with self-ligating and ceramic bracket groups. Class II div 1 malocclusion patients who were treated with conventional bracket system and received LLLT (low level laser therapy), presented higher muscle activity in comparison with the self-ligating bracket system.